2022
DOI: 10.1038/s41467-022-29963-5
|View full text |Cite
|
Sign up to set email alerts
|

ASCL1 activates neuronal stem cell-like lineage programming through remodeling of the chromatin landscape in prostate cancer

Abstract: Treatment with androgen receptor pathway inhibitors (ARPIs) in prostate cancer leads to the emergence of resistant tumors characterized by lineage plasticity and differentiation toward neuroendocrine lineage. Here, we find that ARPIs induce a rapid epigenetic alteration mediated by large-scale chromatin remodeling to support activation of stem/neuronal transcriptional programs. We identify the proneuronal transcription factor ASCL1 motif to be enriched in hyper-accessible regions. ASCL1 acts as a driver of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 75 publications
(123 reference statements)
2
56
0
Order By: Relevance
“…BRN2 was identified as a driver and promising therapeutic target in NEPC. Some of these data have been published 46–48 . Further development of the the first‐in field BRN2 inhibitor is underway.…”
Section: Measuring and Targeting Lineage Plasticity To Prevent Lethal...mentioning
confidence: 99%
See 1 more Smart Citation
“…BRN2 was identified as a driver and promising therapeutic target in NEPC. Some of these data have been published 46–48 . Further development of the the first‐in field BRN2 inhibitor is underway.…”
Section: Measuring and Targeting Lineage Plasticity To Prevent Lethal...mentioning
confidence: 99%
“…Some of these data have been published. [46][47][48] Further development of the the first-in field BRN2 inhibitor is underway. SKCC is located in Philadelphia, Pennsylvania.…”
Section: Next-generation Precision Medicinementioning
confidence: 99%
“…ASCL1 positively regulate neural progenitor differentiation and there is a strong correlation between ASCL1 expression and acquisition of NE-like features ( Narayanan et al, 2019 ). ASCL1 upregulation is an early event following AR signaling suppression ( Nouruzi et al, 2022 ). Hence, ASCL1 is also regarded as an efficient marker for aggressive phenotype and malignant cancer progression ( Vias et al, 2008 ).…”
Section: Other Transcription Factorsmentioning
confidence: 99%
“…This strongly suggests that ASCL1 is highly responsive to androgen and maybe regulated by the AR signaling axis ( Fraser et al, 2019 ). A recent study shows that targeting ASCL1 switches NE lineage to luminal epithelial state ( Nouruzi et al, 2022 ). ASCL1 is enriched in hyper-accessible regions and functions predominantly by disrupting the epigenetic landscape of cancer cells and plays a pivotal role in the early chromatin remodeling in driving PCa NED.…”
Section: Other Transcription Factorsmentioning
confidence: 99%
“…In addition, ATAC-seq and RNA-seq analysis demonstrated that ASCL1 , SOX2 and NEUROD1 expression are shared master regulators between neuroendocrine cancers. ASCL1 and NEUROD1 expressions are mutually exclusive, and are drivers of intra-tumoral heterogeneity, a program that occurs due to distinct H3K27ac genome-wide de novo deposition in SCLC and PCa [ 192 , 193 ]. These data support the association of de novo cis-regulatory elements harboring H3K27ac as a determinant of lineage plasticity in neuroendocrine carcinomas.…”
Section: Pcg Protein Functions and Cell Fate Determinationmentioning
confidence: 99%